Ultrasonic inspection of AA6013 laser welded joints - Passini, Adriano (2011)
Interest in laser beam welding for aerospace applications is continuously growing, mainly for aluminum alloys. The joints quality is usually assessed by non-destructive inspection (NDI). In this work, bead on plate laser welds on 1.6 mm thick AA6013 alloy sheets, using a 2 kW Yb-fiber laser were obtained and inspected by pulse/echo ultrasonic phased-array technique. Good and poor quality welds were inspected in order to verify the limits of inspection, comparing also to X-ray radiography and metallographic inspections. The results showed that ultrasonic phased array technique was able to identify the presence of grouped porosity, through the attenuation of the amplitude of the echo signal. This attenuation is attributed to the scattering of the waves caused by micro pores, with individual size below the resolution limit of the equipment, but when grouped, can cause a perceptive effect on the reflection spectra.